Peta riset terkait literasi digital dalam konteks pendidikan bahasa pada database Scopus: Tinjauan bibliometrik - Aswadi Aswadi; Yayuk Astuti; Geminastiti Sakkir; Suleha Ecca (Universitas Mulawarman, 2026)
This study aims to mapping research, key contributors, collaboration patterns, and the thematic structure of digital literacy research in the context of language education within the Scopus database during the 2015–2024 period. The study employed a quantitative bibliometric approach with a descriptive exploratory design. Data were collected through searches of titles, abstracts, and keywords using a combination of terms related to digital literacy and language education, resulting in 277 documents. Publication metadata were exported and analyzed using VOSviewer to generate network maps of authors, institutions, countries, and keyword co-occurrences. The findings indicate that publication output increased sharply after 2020 and reached its peak in 2024. The most productive authors were Kohnke, Moorhouse, and Tour, while the leading institutions were dominated by Monash University and The Education University of Hong Kong. Geographically, the largest contributions came from Spain, the United States, and Australia, with increasing participation from Indonesia. The thematic analysis produced seven major clusters highlighting online learning, teachers’ digital competence, multimodality, mobile-based learning, and the integration of artificial intelligence in language learning.